Nonlinear analysis of integral bridge - Abdulrazeg, Aeid Ali (2005)
Integral Abutment bridges (IABs) are jointless bridges where the deck is continuous and connected monolithically with abutment walls. The biggest uncertainty in the design of these bridges is the reaction of the soil behind the abutments and adjacent to the piles. The handling of soil-structure interaction in the analysis and design of integral abutment bridges has always been problematic. This study describes the implementation of a 2-D finite element model of IAB system which explicitly incorporates the nonlinear soil response. The superstructure members have been represented by means of three-nodded isoperimetric beam elements with three degree of freedom per node which take into account the effect of transverse shear deformation. The soil mass is idealized by eight nodded isoperimetric quadrilateral element at near field and five nodded isoperimetric infinite element to simulate the far field behavior of the soil media. The non-linearity of the soil mass has been represented by using the Duncan and Chang approach, widely adopted for the hyperbolic model proposed by Kondner and Zelasko. The applicability of this model is demonstrated by analyzing a single span IA bridge. The results have shown that,the result which obtained form nonlinear analysis is almost two times higher that that form linear analysis.